Geomorphological fieldwork - Thornbush, Mary J. (Mary Jessica), 1974-; Allen, Casey D.; Fitzpatrick, Faith A. (Amsterdam : Elsevier, 2014)
Geomorphological Fieldwork addresses a topic that always remains popular within the geosciences and environmental science. More specifically, the volume conveys a growing legacy of field-based learning for young geomorphologists that can be used as a student book for field-based university courses and postgraduate research requiring fieldwork or field schools. The editors have much experience of field-based learning within geomorphology and extend this to physical geography. The topics covered are relevant to basic geomorphology as well as applied approaches in environmental and cultural geomorphology. The book integrates a physical-human approach to geography, but focuses on physical geography and geomorphology from an integrated field-based geoscience perspective.
3.2.3.4.3 -- Balance of Expertise and Compatibility3.2.3.4.4 -- Joint Fieldwork; 3.2.3.4.5 -- Working Alone; 3.2.3.5 -- Communications; 3.2.3.5.1 -- Emergency; 3.2.3.5.2 -- Field Safety; 3.2.3.6 -- Equipment; 3.2.4 -- Leadership of safety culture; 3.2.5 -- Conclusions; Acknowledgments; References; Chapter 4 -- Teaching Geomorphology in the Field; Chapter 4.1 -- Student Learning Styles; 4.1.1 -- Introduction; 4.1.2 -- Methodology; 4.1.3 -- Discussion of results; 4.1.3.1 -- Student perceptions of "novelty spaces"; 4.1.4 -- Educational implications; 4.1.5 -- Conclusions and Recommendations; Acknowledgements.
CIP data; resource not viewed.
References.
Keywords: Geomorphology -- Fieldwork; SCIENCE -- Earth Sciences -- Geography; SCIENCE -- Earth Sciences -- Geology; Electronic books